Comparison of the characteristics of phenolic compounds in Se-enriched kiwifruit and conventional kiwifruit - Ye Zheng; Fang Luo; Li Wang; Shuyi Li; Xuehua Wang; Zhenzhou Zhu (Food Chemistry: X)
While selenium (Se) fortification significantly influences plant secondary metabolism, there has been limited research on its effects on the phenolic profile of kiwifruit. This study aimed to characterize and compare the phenolic profile of Se-enriched and conventional kiwifruit. A total of 463 phenolic compounds were identified. Among these, nine common differential metabolites, including six flavonoids, two phenolic acids, and one lignan (massoniresinol), were identified between Se-enriched and conventional kiwifruit of the same variety. Further comparative analysis of diverse varieties indicated that massoniresinol was the sole differential metabolite. This metabolite was found to be significantly up-regulated in Se-enriched kiwifruit compared to conventional kiwifruit. In addition, correlation analysis showed that the total Se, phenol, and flavonoids content were highly significantly positively correlated with antioxidant activities in kiwifruit. These findings enhance our understanding of the phenolic composition in Se-enriched and conventional kiwifruit and provide a potential biomarker for distinguishing Se-enriched from conventional kiwifruit.